2013
DOI: 10.1080/17477891.2012.738642
|View full text |Cite
|
Sign up to set email alerts
|

Normalized tornado damage in the United States: 1950–2011

Abstract: In 2011, thunderstorms in the United States resulted in 550 deaths from tornadoes and more than $28 billion in property damage, according to data from the US National Oceanic and Atmospheric Administration, with the vast majority of economic losses resulting from tornadoes. This article normalizes U.S. tornado damage from 1950 to 2011, using several methods. A normalization provides an estimate of the damage that would occur if past events occurred under a common base year's societal conditions. We normalize f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…Nevertheless, in 2011 thunderstorms and tornadoes together triggered the $29 billion property damage [33]. Chronological statistics revealed that, 2013 and 2011 stand out as the most destructive years of the past 63 years period and deliver an indication that extreme damage levels have the possibility to upsurge and should social change lead to growing exposure of fortune and property.…”
Section: Tornado Losses (Insurances) In the Usamentioning
confidence: 99%
“…Nevertheless, in 2011 thunderstorms and tornadoes together triggered the $29 billion property damage [33]. Chronological statistics revealed that, 2013 and 2011 stand out as the most destructive years of the past 63 years period and deliver an indication that extreme damage levels have the possibility to upsurge and should social change lead to growing exposure of fortune and property.…”
Section: Tornado Losses (Insurances) In the Usamentioning
confidence: 99%
“…Particularly, we transform the original process into cost that a State has to pay due to tornado damages. To do this, we apply the results of Simmons et al (2013). The F-scale is then transformed into costs, by associating to each grade a cost in the following way: 8689$, 62,440$, 121,141$, 146,564$, 177,824$ and 89,192$ that are, respectively, the mean costs of tornado degrees 0, 1, 2, 3, 4 and 5.…”
Section: Cost Applicationmentioning
confidence: 99%
“…Only in the USA, tornadoes killed, on average, more than 100 people per year from 2004 to 2013 (Simmons et al 2013). Just to give an example of the monetary damages of tornadoes in the USA, in 2013, the estimated cost was about 200 millions of dollars (Simmons et al 2013). In this scenario, the development of techniques to estimate and model the probabilities of these events is needed and can be of great benefit for the society.…”
Section: Introductionmentioning
confidence: 99%
“…Tornadoes may assume different shapes and sizes, but they typically appear as a funnel with the narrower end touching the ground. Tornadoes' damaging paths can surpass 1.5 km wide and 80 km long and the most violent events can cause huge destruction and fatalities [47]. Tornadoes are classified according to their intensity and damage.…”
Section: Us Tornadoes (To)mentioning
confidence: 99%